Cytotoxicity, oxidative stress, and genotoxicity in human hepatocyte and embryonic kidney cells exposed to ZnO nanoparticles - Guan, Rongfa (Springer, 2012)
Traces of zinc oxide nanoparticles (ZnO NPs) used may be found in the liver and kidney. The aim of this study is to determine the optimal viability assay for using with ZnO NPs and to assess their toxicity to human hepatocyte (L02) and human embryonic kidney (HEK293) cells. Cellular morphology, mitochondrial function (MTT assay), and oxidative stress markers (malondialdehyde, glutathione (GSH) and superoxide dismutase (SOD)) were assessed under control and exposed to ZnO NPs conditions for 24 h. The results demonstrated that ZnO NPs lead to cellular morphological modifications, mitochondrial dysfunction, and cause reduction of SOD, depletion of GSH, and oxidative DNA damage. The exact mechanism behind ZnO NPs toxicity suggested that oxidative stress and lipid peroxidation played an important role in ZnO NPs-elicited cell membrane disruption, DNA damage, and subsequent cell death. Our preliminary data suggested that oxidative stress might contribute to ZnO NPs cytotoxicity.